A BIBLIOMETRIC ANALYSIS TO VISUALIZING OF SUSTAINABLE DEVELOPMENT GOAL RESPONSIBLE CONSUMPTION AND PRODUCTION LITERATURE (Third Sector Social Economic Review, 2024)
In this study, it is aimed to examine the development process of academic studies on responsible production and consumption in the world and in Turkey. In this context, first of all, the publications in the Web of Science (WoS) database were scanned on 17.05.2024 using the keyword “Sustainable Development Goals”, and then a bibliometric analysis was carried out with the studies related to the goal of responsible consumption and production from sustainable development goals. The aim of the study is to reveal the development process of the concept of responsible consumption and production within the scope of sustainable development goals in the academic world and to guide future research and studies on this subject. During the bibliometric analysis process, a total of 42,777 publications with the keyword “Sustainable Development Goals” were obtained in the WoS database between 2015-2024. Of these studies, 2,859 were on responsible consumption and production. The publications were analyzed according to research areas, years, countries, institutions, keywords and number of citations. The analyses in the study were conducted using the CiteSpace scientific mapping program version 6.3.R1, which allows bibliometric analysis of scientific works. The country with the highest number of studies on responsible consumption and production is the UK. Our country ranks 45th among the 83 countries with the most citations. It was seen that the most studies on the concept of responsible consumption and society were conducted in 2023.
Keywords: Sustainable development goals; responsible consumption and production; web of science; bibliometrics; CiteSpace.